2004
DOI: 10.1177/0892705704041160
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Binary and Ternary Conductive Composites Based on Polyethylene, Low-melting-point Metal Alloy and Carbon Black

Abstract: This work presents the novel binary and ternary composite materials, based on a low-density polyethylene, metal alloy, which have a melting point close to those of polyethylene and carbon black. Oriented structures were obtained when high-viscosity polyethylene was used as a matrix material. Resistivity of the composite was investigated and nonohmic behavior of the ternary composites was revealed. Temperature dependence of the thermal capacity was studied. The IR (infrared) spectra of the composites were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Besides, the liquid state and low viscosity of LMPMs above melting temperature would reduce the processing viscosity and device abrasion. However, most of the studies on Polymer/LMPM composites concentrated on enhancing the electrically conductive property . The investigations concerned the TCs of polymer/LMPM are rarely reported by far.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the liquid state and low viscosity of LMPMs above melting temperature would reduce the processing viscosity and device abrasion. However, most of the studies on Polymer/LMPM composites concentrated on enhancing the electrically conductive property . The investigations concerned the TCs of polymer/LMPM are rarely reported by far.…”
Section: Introductionmentioning
confidence: 99%
“…We studied the temperature dependence of thermal capacity of the composite and its components and established that the melting point of the metal alloy was T m = 160 • C [11,12]. Both Ipethene 320 and 4203 demonstrated peaks inherent for their glass transition at T s = 110 • C. It is readily seen that the blend has been processed under the temperature T pr > T m > T s , so both polymer and metal alloy were in a liquid state when extruded.…”
Section: Materials and Technology Of Extrusion Dispersion Of The Low-mentioning
confidence: 97%
“…Then the polymer matrix is dissolved and metal powder is removed from the suspension. Extrusion processing of the composites based on polymers and low-melting-point alloys was reported first by Zhang and co-workers [9,10] and Bormashenko et al [11,12]. In those papers, rheology and electrical properties of such composites were discussed.…”
Section: Introductionmentioning
confidence: 96%
“…Zhang et al [21] investigated the rheological properties of polymer/LMTM and found that the LMTM filler decreases the melt viscosity at temperatures above the melting point. Until now, most of the studies on Polymer/LMTM composites concentrated on enhancing the electrically conductive property [1][2][3][4][5]. For instance, Michaeli and Pfefferkorn [1] prepared electrically conductive PA6 with copper fibers and SnZn alloy which was molten during processing.…”
Section: Y C Jia H He * P Yu J Chen X L Laimentioning
confidence: 99%
“…Low melting temperature metal (LMTM), which have melting temperatures less than 231.9°C , are frequently used to prepare electrically conducive polymer composites since their high conductivity, liquid state and low viscosity during processing [1][2][3][4][5][6]. Simultaneously, polymeric materials have attracted increasing interests in the field of thermally conductive materials for the excellent processability, low density and low cost [7].…”
Section: Introductionmentioning
confidence: 99%